Struktur Komunitas Hymenoptera Parasitoid Pada Berbagai Lanskap Pertanian Di Sumatra Barat - Yaherwandi Yaherwandi (Perhimpunan Entomologi Indonesia, 2009)
Understanding how the landscape structure affect the interaction between crops, pests and their natural enemies is a complex problem that can significantly impact on the success or failure of insect biological control. Hymenoptera parasitoids are particularly important natural enemies because of their great diversity and effectiveness as agents of biological control. The objective of this research is to study the diversity of Hymenoptera parasitoid on some vegetables and rice ecosystem in West Sumatera. Hymenoptera parasitoids were sampled using three trapping techniques (farmcop, insect net and yellow pan trap). Species accumulative curves, Jackknife-1 estimator, and indices of diversity were applied to analyze the data. Results indicated that there were 1522 specimen consist of 22 families and 148 species of Hymenoptera parasitoid on agricultural ecosystem in west Sumatera. Braconidae and Ichneumonidae were dominant Hymenoptera parasitoid family in vegetables ecosystem. Contrast, Mymaridae, Diapriidae, and Eulophidae were dominance of Hymenoptera parasitoid famili in rice ecosystem. Diversity of Hymenoptera parasitoid was influenced by the landscape structure. Species richness and diversity were higher in polyculture ecosystem than monoculture.